Escritos urgentes. Nikos Poulantzas y el eurocomunismo de izquierda (Andamios, Revista de Investigación Social, 2011)
This article essays two pathways to analyze theoretical and political productivity of the last book of the Greek-French philosopher Nikos Poulantzas. In the first one, reflecting on his proposal about the articulation between socialism and democracy. In this frame, we emphasize the uniqueness of the author but historically located in what is called Eurocommunism. The second route analyzes the influence of Foucault in Poulantzas’ relational perspective and his approach to power. This time his concerns fall under 68’ event as a moment of visibilization of other subjects, spaces and social resistances. About this influence it is also stressed the irreducible —in my opinion— distance between the two authors, linked to the weighting that each one grants to the class struggle
Keywords: Eurocommunism; representative democracy; participative democracy; labour movement; social movements